2011
DOI: 10.1111/j.1467-9612.2011.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability Cline in VP Ellipsis

Abstract: This paper lays the foundations for a processing model of relative acceptability levels in verb phrase ellipsis (VPE). In the proposed model, mismatching VPE examples are grammatical but less acceptable because they violate heuristic parsing strategies. This analysis is presented in a Minimalist Grammar formalism that is compatible with standard parsing techniques. The overall proposal integrates computational assumptions about parsing with a psycholinguistic linking hypothesis. These parts work together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 68 publications
3
61
1
19
Order By: Relevance
“…This resembles the pattern of results reported by Kim et al (2011), with structural mismatch selectively degrading sentences with VPE. In addition, Experiment 1 shows that sentences featuring a Cause-Effect relation were less sensitive to structural mismatch in general-not only in sentences containing VPE.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This resembles the pattern of results reported by Kim et al (2011), with structural mismatch selectively degrading sentences with VPE. In addition, Experiment 1 shows that sentences featuring a Cause-Effect relation were less sensitive to structural mismatch in general-not only in sentences containing VPE.…”
Section: Discussionsupporting
confidence: 71%
“…Kertz (2008) found that Frazier and Clifton (2006)'s finding-that Cause-Effect sentences were worse overall than Resemblance sentences-was true of both the VPE sentences and their unelided counterparts. This contrasts with another magnitude estimation study by Kim et al (2011), which tested both voice mismatch and category mismatch (nominal antecedents) in VPE and unelided controls, and found a mismatch penalty only in sentences containing ellipsis.…”
Section: Experiments 1: Structural Effects Are Modulated By Discourse contrasting
confidence: 47%
See 3 more Smart Citations